Mitogen-activated protein kinase-activated protein kinase 2 deficiency reduces insulin sensitivity in high-fat diet-fed mice. - Jan Freark de Boer; Arne Dikkers; Angelika Jurdzinski; Johann von Felden; Matthias Gaestel; Udo Bavendiek; Uwe J F Tietge (PLoS ONE, 2014)
Adipose tissue inflammation is considered an important contributor to insulin resistance. Mitogen-activated protein kinase-activated protein kinase 2 (MK2) is a major downstream target of p38 MAPK and enhances inflammatory processes. In line with the role of MK2 as contributor to inflammation, MK2-/- mice are protected against inflammation in different disease models. Therefore, MK2 is considered an attractive therapeutic target for the treatment of chronic inflammatory diseases. This study tested the impact of MK2-deficiency on high-fat diet (HFD)-induced adipose tissue inflammation and insulin resistance. After feeding MK2-/- and WT control mice a HFD (60% energy from fat) for 24 weeks, body weight was not different between groups. Also, liver weight and the amount of abdominal fat remained unchanged. However, in MK2-/- mice plasma cholesterol levels were significantly increased. Surprisingly, macrophage infiltration in adipose tissue was not altered. However, adipose tissue macrophages were more skewed to the inflammatory M1 phenotype in MK2-/- mice. This differerence in macrophage polarization did however not translate in significantly altered expression levels of Mcp-1, Tnfα and Il6. Glucose and insulin tolerance tests demonstrated that MK2-/- mice had a significantly reduced glucose tolerance and increased insulin resistance. Noteworthy, the expression of the insulin-responsive glucose transporter type 4 (GLUT4) in adipose tissue of MK2-/- mice was reduced by 55% (p<0.05) and 33% (p<0.05) on the mRNA and protein level, respectively, compared to WT mice. In conclusion, HFD-fed MK2-/- display decreased glucose tolerance and increased insulin resistance compared to WT controls. Decreased adipose tissue expression of GLUT4 might contribute to this phenotype. The data obtained in this study indicate that clinical use of MK2 inhibitors has to be evaluated with caution, taking potential metabolic adverse effects into account.